(untitled) (Global Journal of Science Frontier Research, 2016)
This paper applies the Markov switching heteroscedasticity model to stock return for India. The Markov switching model in our study takes into account the chance of regime shift, a possibility outside the purview of the GARCH model. Our finding tells us that the high variance of the transitory component tends to be short lived.